HUBUNGAN TINGKAT PENGETAHUAN KONSERVASI LAHAN GAMBUT DENGAN TINGKAT PARTISIPASI PETANI DALAM UPAYA PENCEGAHAN KEBAKARAN LAHAN GAMBUT DI DESA GAMBUT JAYA KECAMATAN SUNGAI GELAM KABUPATEN MUARO JAMBI TAHUN 2017 - Oktiana, Cichi; Tjahjono, Heri; Sriyono, Sriyono (Geo-Image, 2017)
Research purpose: 1) To know the level of farmer’s knowledge about peatlands conservation, 2) To know the level farmer’s participation in preventing peatlands fire, 3) To know the relation between the knowledge about peatlands conservation and the level of farmer participation in preventing peatlands fire. Population: 364 of farmers. 10% sample or 38 farmers who taken by proportionate area random sampling. The techniques in collecting data are test, questionnaire, observation and documentation. Descriptive analysis technique and product moment correlation are used in analysis the data. The result of the research are the level peatlands conservation knowledge and the level of farmer participation in peatlands fire prevention are included in medium category. The relation between the level of peatlands conservation knowledge and the level of farmer participation in peatland fire prevention is strong, where, r hitung 0,7802 > r table 0,468. Its means that the higher the knowledge of peatland conservation the higher the level of farmer participation in fire prevention.